Data supporting: 'Fibre-optic measurement of strain and shape on a helicopter rotor blade during a ground run: data for the measurement of shape' - Kissinger, Thomas; James, Stephen W.; Weber, Simone; Mullaney, Kevin; Chehura, Edmon; Barrington, James; Staines, Stephen; Tatam, Ralph P. (Cranfield University, 2022)
FSI_Phase_Data_Shape_CORD.csv contains the raw phase data from the three Fibre Segment interferometry array installed on the Direct Optical Fibre Shape Sensing Rod described in the paper: "Fibre-optic measurement of strain and shape on a helicopter rotor blade during a ground run - part 2: measurement of shape", Smart Materials and Structure, online 25 May 2022. Shape_Data_Vertical_CORD.csv contains the processed shape data in the vertical (flapping) direction, for the T&B2 ground run. Note that the position measurements are relative to the first FSI reflector on the rod, not to the centre of rotation of the blade. Shape_Data_Horizontal_CORD.csv contains the processed shape data n the horizontal (lagging) direction, for the T&B2 ground run. Note that the position measurements are relative to the first FSI reflector on the rod, not to the centre of rotation of the blade.
Keywords: Fibre Bragg Grating Sensors'; 'Fibre optic sensors'; 'fibre segment interferometry'; 'Strain measurement'; 'Interferometry'; 'Helicopters'; 'rotor blades'; 'Aerospace Engineering'; 'Aerospace Structures'; 'Engineering Instrumentation'; 'Photonics and Electro-Optical Engineering (excl. Communications)'; 'Photonics; Optoelectronics and Optical Communications'